Lectures on the history of philosophy study guide (tutorial) - Pecherskikh S. P. (Ижевск, ИГМА, 2024)
The manual is intended for international students studying the discipline «Philosophy» in English. The manual is designed to help students improve their ideological competence, develop skills for independent analysis and interpretation of the most important ideological and value systems in the context of world historical development. The manual contains material on all historical epochs of the development of world philosophy from Ancient India to modern Western and Russian philosophy. The content of the main 10 historical periods of the development of philosophy is set out in 14 developed lectures and control questions for them. The manual on the discipline «Philosophy» is compiled in accordance with the modern Russian educational standard.